DETERMINING THE RELATIONSHIP BETWEEN EMPATIC TENDENCY AND CRITICAL THINKING INCLINATION OF FOOTBALL COACHES - ZAMBAK Ö; ACET M.; CENGIZ R.; MUMCU H. E.; KUSAN, O.5 (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
The main target of this research is to determine the relation between Empatic Tendency and Critical Thinking Inclination of football coaches. For that purpose, California Critical Thinking Inclination (CCTDI), improved by Facione & Giancarlo, adopted in turkish by Kökdemir (2003), and Empathic Tendency Scale (ETS), improved by Dökmen (Dökmen, 1988), were used in this research. The research group consisted of 174 football coaches worked in three cities of Turkey, Aydın, Uşak, Denizli, during the 2015-2016 football season. Spss 16.0 statistical program was used for data analysis to make use of its percentage and frequencies. Kolomogrov-Smirnof test was used to determine whether the data from two dependent variables to show a normal distribution or not. To interpret the data, t-test, Pearson correlation analysis for examining relation between 2 dependent groups, non-parametrik test for lack of normal distribution of sub-dimensions, and test of one way anova for more than two goups, were used. According to findings of the research, there are statistically significant difference between CCTDI scores (t=-9,641) and education level of coaches (p<0.05). It has been observed that football coaches with graduate and post graduate education has higher CCTDI result more than coaches with college education. There are statistically significant difference between the result of ETS scores (t=-17,451) and education level of coaches (p<0.05). It has been confirmed that football coaches with graduate and post graduate education has higher CCTDI result more than coaches with high-school according to the aspect of the difference. In conclusion it is understood that there are significantly difference in the ETS scores of football trainers when educational level of them and their parents, monthly income are, however, it has been concluded that there is no difference regarding between their professional seniority, age ranges and ETS scores. By the way, it has been concluded that the educational level of football trainers, educational level of parents, monthly income are determinant on tendency of critical thinking, but professional seniority and age ranges are not determinant on the tendency of critical thinking.